Technology Integration Framework for Fast and Low Cost Handovers—Case Study: WiFi-WiMAX Network. (23rd May 2010) - Kassab, Mohamed; Bonnin, Jean-Marie; Belghith, Abdelfettah
Abstract : The Next Generation Wireless Networks (NGWNs) are seemed to be heterogeneous networks based on the integration of several wireless technologies. These networks are required to achieve performances equivalent to classic wireless networks by ensuring the continuity of communications and the homogeneity of network management during horizontal and vertical handovers. This task is even more important when management services, like security and quality of service (QoS), are deployed at access technology level. In this paper, we propose a framework for heterogeneous wireless technology integration based on network architecture skeleton and a handover management mechanism. This framework optimizes the layer-2 handover procedure to achieve performances required by sensitive applications while ensuring the minimization of signaling overhead required for operated networks. As an application example, we make use of this framework to propose a heterogeneous network based on WiFi and WiMAX technologies. We present an application example of the framework using the specification of a WiFi-WiMAX network. We propose several performance evaluations based on simulation tests based on this application. The latter confirm the efficiency of handover delay optimization and the minimization of management signaling costs.